Gas tungsten arc welding of as-rolled CrMnFeCoNi high entropy alloy - Oliveira, J. P. (2020)
Fundacao para a Ciencia e Tecnologia (FCT)- project UID/EMS/00667/2019 (UNIDEMI). FMBF acknowledges funding of CENIMAT by FEDER through the program COMPETE 2020 and National Funds through FCT-Portuguese Foundation for Science and Technology, under the project UID/CTM/50025/2019 and FCT/MCTES. This work was supported by the Future Material Discovery Project of the National Research Foundation of Korea (NRF) funded by the Ministry of Science and ICT of Korea (NRF-2016M3D1A1023383). NFFA-Europe Transnational Access Activity (project reference Nf-20010136 EC and ID-806).